The Effectiveness of the Seven Habits Program to Enhance Elementary Students’ Character in the Digital Era - Damayanti, Anggun Dwi; Widiyono, Dwi; Kasanah, Uswatun (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
In response to the growing challenges of character development in the digital era, this study investigates the effectiveness of implementing the Seven Habits of Great Indonesian Children program in enhancing the character of elementary school students. This qualitative case study was conducted at SD Negeri 9 Purwodadi and involved 15 purposively selected participants, including one principal, four teachers, and ten upper-grade students (grades 4–6) who were actively engaged in the program. Data collection methods included interviews, classroom observations, and documentation of relevant school activities. The data were analyzed using Miles and Huberman’s interactive model, which comprises data reduction, data display, and conclusion drawing. The findings demonstrate that the Seven Habits program was effectively implemented and significantly contributed to students’ character development, particularly in fostering independence, active learning, collaboration, leadership, and responsibility. Supporting factors included structured routines, motivational strategies, creative teaching methods, and positive reinforcement. However, several challenges were also identified, such as limited instructional time, insufficient learning media, varying levels of student motivation, and weak parental involvement. These results suggest the need for enhanced school–parent collaboration, increased access to creative educational resources, and targeted teacher training in character education. Future research is recommended to assess the program’s long-term impact and its applicability across different educational contexts.